OPTIMALISASI PEMASARAN DIGITAL PADA PRODUK MINUMAN HERBAL POSBINDU DAHLIA INDAH - Happy Egi Afriano; Nabillaputri Widiauliannisa; Septia Pratiwi; Dika Aisyah Veronika; Julian Bongsoikrama; Justin Bongsoikrama; Bayu Satria Pratama; Anastasia Putri Kristiani (Jurnal Padamu Negeri, 2025)
This the community engagement aims to optimize the digital marketing of herbal beverage products developed by Posbindu Dahlia Indah as an effort to improve the competitiveness of local MSMEs. The program was conducted using a participatory approach through observation, interviews, training, and both pre-test and post-test evaluations. The results showed a significant increase in participant understanding, with an average improvement from 46.5% to 85.5%. The training covered digital marketing, branding strategies, social media management, and production and distribution planning. These findings indicate that digital marketing-based training contributes positively to enhancing the capacity of Posbindu cadres in managing their businesses. Challenges remain, such as limited production tools, non-eco-friendly packaging, and lack of product certification. However, opportunities exist in developing butterfly pea tea bags and expanding market reach through marketplace platforms and external partnerships. The study recommends strengthening digital strategies, packaging innovation, and certification processes as sustainable steps for the growth of local herbal businesses.